Penerapan Manajemen Risiko untuk Meningkatkan Kinerja Industri Perbankan di Indonesia - Erman, Nilam; Winario, Mohd. (AL-Muqayyad, 2024)
This research aims to determine the implementation and control of risk management in the banking industry in Indonesia. This study uses a qualitative method. The results of this research indicate that the application of risk management in the banking industry must be implemented considering the increasing number of types of crime in the banking world. The application of risk management in the banking industry must be adjusted to the objectives, business policies, size and complexity of the business and the capabilities of the bank itself. Business complexity is the diversity of product transactions/business networks. Meanwhile, bank capabilities include financial capabilities, supporting infrastructure and human resource capabilities. How to manage risk management in the banking industry can be carried out with several efforts, including determining risks, weighing risks, observing and controlling these risks.